Hepatocyte‐Targeted Lipid Nanoparticle Delivery of HERC2 Plasmid Controls Drug‐Induced Hepatotoxicity by Limiting β‐Catenin‐Regulated CYP2E1 Expression - Yunzhi Liu; Qishan Xu; Yan Liu; Sihang Cao; Jialiang Luo; Zhuojun Zheng; Jia Zhou; Xiao Lu; Liyun Zhang; Yanan Tan; Qingyun Chen; Daming Zuo (Advanced Science)
Abstract Understanding the molecular mechanisms that bridge hepatic inflammation and liver injury is crucial for developing effective therapeutic strategies for drug‐induced liver injury (DILI) management. HECT domain and RCC1‐like domain 2 (HERC2) belongs to the large Herc family of ubiquitin E3 ligases, which are implicated in tissue development and inflammation. The observation reveals a pronounced HERC2 expression in specific hepatocyte subsets that proliferate in response to DILI in humans, prompting an investigation into the role of HERC2 in distinct DILI progression. Under the APAP challenge, liver‐specific HERC2‐deficient mice suffer more severe liver damage. Integrated single‐cell RNA sequencing analysis unveils a negative correlation between HERC2 and CYP2E1, a vital metabolic enzyme for xenobiotics, in hepatocytes from APAP‐challenged mice. Mechanistically, HERC2 interacts with β‐catenin to promote its ubiquitination, thereby governing CYP2E1 transcriptional regulation. Targeted hepatic delivery of lipid nanoparticle‐encapsulated HERC2‐overexpressing plasmid markedly reduces liver damage caused by APAP overdose. Collectively, these findings elucidate a previously unrecognized protective role of HERC2 in protecting against acute liver injury associated with drug metabolism disorders, highlighting its potential as a therapeutic target in treating DILI.